PEMANFAATAN BATANG KELAPA DAN KAYU KARET SEBAGAI BAHAN BAKU GLULAM - Harsono, Dwi (Jurnal Riset Industri Hasil Hutan, 2012)
The research of coconut and rubber wood utilization as raw material for glulam has been done. This research aims to optimize the function of rubber wood and palm stem by the incorporation of technology and adhesion to wood products in the form of building construction materials. In addition, knowing the physical and mechanical properties of glulam based on three variations of the type of timber (rubber wood, coconut, coconut stem wood + rubber), and various number of layers (5 layers, 6 layers, and 7 layers). Each combination treatment was repeated three times. The best mechanical physical properties of glulam for type of rubber wood, with 7 layers.Â Keywords : glulam, coconut wood, rubber wood, characters physical, characters mechanic